2012
DOI: 10.5194/bg-9-1085-2012
|View full text |Cite
|
Sign up to set email alerts
|

Budget of N<sub>2</sub>O emissions at the watershed scale: role of land cover and topography (the Orgeval basin, France)

Abstract: Abstract. Agricultural basins are the major source of N 2 O emissions, with arable land accounting for half of the biogenic emissions worldwide. Moreover, N 2 O emission strongly depends on the position of agricultural land in relation with topographical gradients, as footslope soils are often more prone to denitrification. The estimation of land surface area occupied by agricultural soils depends on the available spatial input information and resolution. Surface areas of grassland, forest and arable lands wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The importance of landscape position on N 2 O emissions has been documented by other studies [ Pennock et al , ; Corre et al , ], which found greater N 2 O emissions in the valley bottom than in the ridgetop or midslope positions. Differences in moisture content along the slope usually explain the N 2 O flux variability [ Vilain et al ., , ; Negassa et al ., ], with higher fluxes in the lower positions closely correlated with the higher WFPS. However, our approach involved standardized soil moisture levels across the treatments, and we still observed position‐driven variations of N 2 O emission with lower N 2 O emitted at the steeply sloping plots when compared with flat plots (ridgetop and valley bottom plots).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of landscape position on N 2 O emissions has been documented by other studies [ Pennock et al , ; Corre et al , ], which found greater N 2 O emissions in the valley bottom than in the ridgetop or midslope positions. Differences in moisture content along the slope usually explain the N 2 O flux variability [ Vilain et al ., , ; Negassa et al ., ], with higher fluxes in the lower positions closely correlated with the higher WFPS. However, our approach involved standardized soil moisture levels across the treatments, and we still observed position‐driven variations of N 2 O emission with lower N 2 O emitted at the steeply sloping plots when compared with flat plots (ridgetop and valley bottom plots).…”
Section: Discussionmentioning
confidence: 98%
“…For a detailed description of the Orgeval river basin, please refer to Vilain et al . (). Observed hourly precipitation and discharge data from 1970 to 2012 allowed the construction of IDF curves for different return periods ( T r ) and the determination of yearly discharge maxima.…”
Section: Description Of Case Studiesmentioning
confidence: 97%
“…1). In addition, the Orgeval River in an agricultural experimental catchment (Vilain et al 2012) was also monitored during year 2011 (n=9) (Fig. 1).…”
Section: Sampling Sites / Campaignsmentioning
confidence: 99%